Pelatihan Peningkatan Keterampilan Berbasis Proyek yang Menyenangkan untuk Guru dalam Merdeka Belajar di SDN Wasur 2 Kabupaten Merauke - Hanipah, Sri; Ginting, Syahfitriani Br (Jurnal Pengabdian UNDIKMA, 2025)
This community service activity aims to enhance the competencies of teachers at SDN Wasur 2 in implementing enjoyable project-based learning within the framework of the Kurikulum Merdeka. The implementation methods included training and mentoring, involving 22 teacher participants. The evaluation instrument utilized a questionnaire comprising 20 statements, and the data analysis technique employed a t-test to identify differences in knowledge before and after the activity. The results of the community service indicated that the training and mentoring positively impacted the teachers' skills in implementing enjoyable project-based learning. This is evident from the positive responses to the training provided. Teachers felt that the training offered new inspiration for enhancing their teaching creativity and expressed increased confidence in using project-based learning methods after the training. The implications of this activity included the improved ability of teachers to implement enjoyable project-based learning and to create engaging lessons for students.